FORMULASI STRATEGI DENGAN PENDEKATAN QUANTITATIVE STRATEGIC PLANNING MATRIX PADA USAHA TEENIES BOUTIQUE - Nur Azizah Febriyanti Yulizar (2023)
Teenies Boutique is a business that was established in 2019 and is a leading business engaged in the online market in the field of hijab fashion. It has a variety of hijab product models according to existing trends. The sales at the Teenies Boutique decreased because of the absence of a marketing strategy to survive among competitors. To overcome these challenges, companies must design appropriate marketing strategies. The input stage, which is the first, involves the identification of both internal and external elements. The matching stage comes next, where appropriate strategies are chosen using the IE matrix, SPACE matrix, and SWOT analysis. Strategies including market penetration, market development, and product development are the outcomes of this matching stage. The final step is to evaluate and select the most effective alternative strategy using the QSPM. One of the highest-ranked alternative strategies is to increase promotion through social media platforms such as Instagram, TikTok, WhatsApp, Facebook, and Twitter. By utilizing social media, Teenies Boutique can expand its market share and increase its sales by attracting potential buyers. The total attractiveness score (TAS) for this strategy is 5.503, which denotes a high level of attraction. By implementing this strategy, Teenies Boutique can increase its visibility and achieve greater business success.